International Encounters: Higher Education and the International Student Experience - Wu, Yi-Chin (Journal of International Students, 2020)
In light of the exponential rise in international student numbers for decades—a rise that has narrowed in the last 2 years—many higher education institutions around the world have been called to consider questions around the value of the internationalization of higher education. A changing view of internationalization’s benefits was identified in a global survey conducted by the International Association of Universities. The results indicated that “enhanced international cooperation and capacity building” has become a more important benefit, and neither “increased international awareness of/deeper engagement with global issues” nor “quality of teaching and learning” were in the top three benefits at the global level (Marinoni et al., 2019). Therefore, it is more important than ever for higher education professionals to rethink current pedagogy around international student instruction. International Encounters is among the newest contributions to ongoing discussions of international students’ learning experiences in higher education.